Polypharmacy in a semirural community in Chile: Results from Maule Cohort. Issue 3 (10th February 2020) - Oyarzún‐González, Ximena; Ferreccio, Catterina; Abner, Erin L.; Vargas, Claudio; Huidobro, Andrea; Toro, Pablo
Abstract : Purpose: Although polypharmacy in younger populations is a growing public health concern, most studies addressing polypharmacy focus on elderly populations. Thus, polypharmacy is not yet well understood in younger populations. Methods: Baseline data from the Maule Cohort (MAUCO) (adults aged 38‐74 years) were used to study the prevalence of polypharmacy and associated participant characteristics using logistic and zero‐inflated negative binomial regressions. Factors studied include age, sex, self‐rated health, education, smoking, obesity, diabetes, hypertension, and other chronic conditions. Results: Polypharmacy was reported by 10% of participants overall, with higher prevalence among older (≥60 years) vs middle aged (<60 years) participants (overall: 20.9% vs 6.0%, P < .0001; for those reporting any medication use: 30.2% vs 15.9%, P < .0001). Middle‐aged adults reported different patterns of medication use by polypharmacy status, while older adults reported similar medication use patterns regardless of polypharmacy. Diabetes, hypertension, dyslipidemia, cardiovascular diseases, hypothyroidism, and osteomuscular diseases were significantly associated with polypharmacy. Analyses also revealed that there are MAUCO participants who are potentially being undertreated for conditions like depression. Conclusions: Research into medication use among younger and middle‐aged adults and development of possible tools to deprescribe medications in this population are warranted. However, it is important that patients who need treatment receive it, and so both potential overtreatment and undertreatment need further study in this population.